PENGARUH MODIFIKASI PERMAINAN LEMPAR TANGKAP BOLA TERHADAP KOORDINASI GERAK MANIPULATIF ANAK TUNAGRAHITA RINGAN SISWA SMPLB-C ALPHA KUMARA WARDHANA II SURABAYA - ZAINAL ARIFIN, MUHAMMAD (Jurnal Kesehatan Olahraga, 2017)
The motoric development of tunagrahita children is not fast than the motoric development of natural children. Because it influenced by the intellectual ability some child and less of coordination movement is the indicator motoric which had the tunagrahita children. The purpose of this research is to know the influence of modification throw-catch ball game for coordination move manipulative. This research use experimental apparent research with use pre test post test plan. The sample of this research use 14 sample with use purposive sampling. The instruments of this research use motor fitness test with use modification throw on the target with move coordination.The result of this research got the average coordination move manipulative on pre test is 4,64 times of pitch and post test is 5,50 times of pitch. Based on normality data pre test got tabel is bigger from hitung (5,991> 1,107) and post test (5,991 > 1,315), so the distribution data is normal. The accounting of difference test average of coordination move manipulative before and after given modification throw-catch ball game got thitung  2,747, the value ttabel with significance 0,05 with df = 13 is 1,771. Because thitung is bigger from ttabel (2,747 > 1,771). So can take the conclusion there is the influence of modification throw-catch ball game for coordination move manipulative.